Atom probe tomography of nanoscale electronic materials. (January 2016) - Larson, D.J.; Prosa, T.J.; Perea, D.E.; Inoue, K.; Mangelinck, D.
Abstract: Abstract : As the characteristic length scale of electronic devices shrinks, so does the required scale for measurement techniques to provide useful feedback during development and fabrication. The current capabilities of atom probe tomography (APT), such as detecting a low number of dopant atoms in nanoscale devices or studying diffusion effects in a nanowire (NW), make this technique important for metrology on the nanoscale. Here we review recent APT investigations applied to transistors (including regions such as gate oxide, channel, source, drain, contacts, etc.), heterogeneous dopant incorporation in NWs, and Pt-based nanoparticles.